Flood disasters in the Changjiang River and their geo-environmental implications (Journal of Nepal Geological Society, 2001)
The archaeological records of past 5,000 years revealed that a period of high (13.6 m) flood occurred in the Changjiang River in 2,000 years BP. A serious flood disaster happened in the middle and lower reaches of the Changjiang River in 1998. This event reverberated through the whole country and led to the very important attention by many scientists and engineers.In this paper, it is proposed to carry out the following three flood control measures. The first is to improve the flood control standard, which includes dredging river course and reinforcing dykes or dams. The second is to dig a channel through the Dongjing River (an old course of the Changjiang River) to divert the flood for avoiding the simultaneous flooding from different rivers and to remove the flood disaster for the Wuhan City. The third is to form gradually a great lake across the Changjiang River to contain the Dongting Lakeand Jianghan Lakes, which will supp ly the fresh water to be enough for the society and economic development of the middle China in the 21st century.